MANAGEMENT AND TRAINING ON AEDES AEGEPTY MOSQUITO NEST ERADICATION (PSN) AT AL-HIJRAH ISLAMIC BOARDING SCHOOL, POLMAN - Hosni Mubarak, Muhammad; Al Hijrah, Muh. Fauzar; ., Heriyati (LPPM Univ. Ibn Khaldun Bogor, 2023)
Background: The eradication of Aedes aegypti mosquito nests in Islamic boarding schools is very important because Aedes aegypti is the main vector of dengue fever and Zika virus. If not controlled, this mosquito population can spread and cause disease outbreaks that endanger public health, especially Islamic boarding school students. Objective: This activity aims to increase the knowledge, skills as well as motivation of coaches and students to play an active role in preventing dengue fever by eradicating mosquito nests. Method: Management activities and training on mosquito nest eradication (PSN) aedes aegepty at Al-Hijrah Islamic Boarding School consist of PSN training activities will be carried out with lectures, demonstrations, and discussions between speakers and participants, then to find out the effects of counseling, the community service team conducts pre and post tests on students about PSN. Results: based on the results of this study, the number of students and satriawati who participated was 21 people, including 12 students of male gender and 9 students of female gender. It is known that there is an increase in knowledge. The data were abnormally distributed, so the Wilcoxon test was used to determine whether there were differences in the level of knowledge before and after exposure to material related to mosquito nest eradication. The results of the Wilcoxon test show that the value of Asymp.GIS (2-tailed) 0.005 (p<0.05) so that it can be concluded that there are differences in the level of knowledge before and after education activities are carried out about the eradication of dengue mosquito nests. Conclusion: it was concluded that there were differences in the level of knowledge before and after the education activities on the eradication of dengue mosquito nests.